Effects of some commonly used drugs on cognitive functions - O. D. Ostroumova; E. V. Shikh; E. V. Rebrova; A. G. Abrosimov (Неврология, нейропсихиатрия, психосоматика, 2018)
The paper discusses the effects of drugs from different pharmacological groups on cognitive functions. It details the impact of drugs used to treat nervous system, cardiovascular, gastrointestinal, respiratory, and endocrine diseases on cognitive functions. It is emphasized that many drugs exert both negative and (less frequently) positive effect on cognitive functions, but it is especially pronounced in drugs used to treat nervous system diseases. There is evidence suggesting that different representatives of a number of pharmacological groups have no class effect on cognitive functions.